26th Annual Conference of the German Crystallographic Society March 5-8, 2018, Essen, Germany : abstracts. (Zeitschrift für Kristallographie. Supplement issue ;, 2018)
"Zeitschrift für Kristallographie. Supplement, Volume 38, presents the complete abstracts of all contributions to the 26th Annual Conference of the German Crystallographic Society in Essen (Germany) 2018"--